The role of teeth in mammal History - Lílian Paglarelli Bergqvist (Universidade Estadual de Campinas, 2015)
Teeth are more than hard structures for cutting, grinding and/or crushing food. Teeth, living or dead, have much to contribute to the study of ecology, paleontology, functional morphology and systematic. They are the most common mammal body part recovered in paleontological and archaeological assemblages, and one of the easiest tools for assessing mammal evolution. The present day human teeth morphology is a result of mammal evolution, started about 225 millions of years ago. From a simple cone to a complex and diverse pattern of cones and ridges, tooth evolved (in part) as a response to the changes in Earth environment. This paper looks for presenting an overview, of the history of mammal teeth, since its origin to the present day diversity, as long as the importance of teeth for mammals, emphasizing the contribution of paleontology to recent human tooth design, function and nomenclature